Activation of Cell Surface Bound 20S Proteasome Inhibits Vascular Cell Growth and Arteriogenesis. (4th June 2015) - Ito, Wulf D.; Lund, Natalie; Zhang, Ziyang; Buck, Friedrich; Lellek, Heinrich; Horst, Andrea; Machens, Hans-Günther; Schunkert, Heribert; Schaper, Wolfgang; Meinertz, Thomas
Abstract : Arteriogenesis is an inflammatory process associated with rapid cellular changes involving vascular resident endothelial progenitor cells (VR-EPCs). Extracellular cell surface bound 20S proteasome has been implicated to play an important role in inflammatory processes. In our search for antigens initially regulated during collateral growth mAb CTA 157-2 was generated against membrane fractions of growing collateral vessels. CTA 157-2 stained endothelium of growing collateral vessels and the cell surface of VR-EPCs. CTA 157-2 bound a protein complex (760 kDa) that was identified as 26 kDa α 7 and 21 kDa β 3 subunit of 20S proteasome in mass spectrometry. Furthermore we demonstrated specific staining of 20S proteasome after immunoprecipitation of VR-EPC membrane extract with CTA 157-2 sepharose beads. Functionally, CTA 157-2 enhanced concentration dependently AMC (7-amino-4-methylcoumarin) cleavage from LLVY ( N -Succinyl-Leu-Leu-Val-Tyr) by recombinant 20S proteasome as well as proteasomal activity in VR-EPC extracts. Proliferation of VR-EPCs (BrdU incorporation) was reduced by CTA 157-2. Infusion of the antibody into the collateral circulation reduced number of collateral arteries, collateral proliferation, and collateral conductance in vivo. In conclusion our results indicate that extracellular cell surface bound 20S proteasome influences VR-EPC function in vitro and collateral growth in vivo.